Optimization of Blanching Treatment for Banana - Khar, Abhijit; Chandra, Pitam; Pasrsad, Rajinder; Dash, Sanjaya K (Journal of Agricultural Engineering, 2003)
The study was made to optimize hot water, steam and microwave blanching of banana (Dwarf Cavendish) slices with respect to the total inactivation of peroxidase and polyphenoloxidase for subsequent microwave assisted dehydration. It was found that hot water blanching (97degree C) of 5 min.; steam blanching (live steam) of 4 min.; and microwave blanching (700 W) of 1.5 min. was sufficient to completely inactivate both peroxidase and polyphenoloxidase and thereby ensuring no enzymatic browning in subsequent dehydration process.